ON THE L-DUALITY OF A FINSLER SPACE WITH (α,β )-METRIC (α+β)^2/α - GAUREE SHANKER (Romanian Journal of Mathematics and Computer Science, 2015)
The geometry of higher order Finsler spaces were studied in ([1], [6], [10]). The theory of higher order Lagrange and Hamilton spaces were discussed in ([8], [9],[11]). Some special problems concerning the L-duality and classes of Finsler spaces were studied in ([3], [13]) . Various geometers such as ([2], [3], [4]) etc. have studied the L-dual of Randers, Kropina and Matsumoto space. In this paper we have obtained the L-dual of a special (α,β)-metric (α+β)^2/(α). .